2007
DOI: 10.1002/humu.20611
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of translocation breakpoints in 2q37 is associated with overexpression of NPPC in patients with a similar overgrowth phenotype

Abstract: Overexpression of the C-type natriuretic peptide, encoded by the NPPC gene in 2q37.1, was recently reported in a patient presenting an overgrowth phenotype and a balanced t(2;7)(q37.1;q21.3) translocation. We present clinical, cytogenetic, and molecular data from two additional patients carrying balanced translocations involving the same 2q37.1 chromosome band and chromosomes 8 and 13, respectively. The clinical phenotype of these patients is very similar to the first patient described. In addition to the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 13 publications
1
57
1
Order By: Relevance
“…Convincing evidence from the last decade shows that CNP is essential for postnatal skeletal growth (Chusho et al 2001). For example, contrived (Olney 2006) or spontaneous genetic modifications within the CNP signalling pathway in rodents (Potter et al 2006), cattle (Koltes et al 2009) and humans (Bartels et al 2004, Moncla et al 2007) uniformly and concordantly profoundly affect linear growth velocity. That this may also be true of normal growth is suggested by findings from genome-wide association studies linking the adult height of humans with several genes affecting CNP's activity (Lango Allen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Convincing evidence from the last decade shows that CNP is essential for postnatal skeletal growth (Chusho et al 2001). For example, contrived (Olney 2006) or spontaneous genetic modifications within the CNP signalling pathway in rodents (Potter et al 2006), cattle (Koltes et al 2009) and humans (Bartels et al 2004, Moncla et al 2007) uniformly and concordantly profoundly affect linear growth velocity. That this may also be true of normal growth is suggested by findings from genome-wide association studies linking the adult height of humans with several genes affecting CNP's activity (Lango Allen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…At physiologic concentrations, the mutated natriuretic peptide CNP lbab is unlikely to cause significant elevations in cGMP, which would fail to trigger the down stream signal transduction pathways that normally ensue after CNP release in bone tissue. Recently, human chromosomal 2:7 translocations located close to the NPPC gene were identified that result in elevated CNP mRNA expression, increased CNP protein levels, and skeletal overgrowth [3,20]. Whether mutations exist in the coding region of CNP that modify human skeletal growth has yet to be reported, but based on the lbab −/− mouse, we believe this scenario is likely.…”
Section: Discussionmentioning
confidence: 95%
“…Three patients carrying a chromosomal translocation at the chromosomal region 2q37.1 were shown to have a breakpoint within the DIS3L2 gene at intron 5 (2 patients) and intron 6 (1 patient) [33][34][35]. The symptoms of these patients included skeletal overgrowth and malformations, leading to long, slender fingers, curvature of the hands and feet (arachnodactyly), lack of apoptosis between digits (mild syndactyly), and abnormal curvature of the spine (severe scoliosis).…”
Section: Human Diseases Associated With Dis3l2mentioning
confidence: 99%